The use of the case method during the teaching of the discipline «Age physiology and school hygiene» (Physical Culture and Sport: Scientific Perspective, 2024)
The article considers one of the popular interactive methods in the modern education system - the case study. Teachers use various methods and tools to conduct the educational process. Learning new information through practical tools allows students of higher education to learn the material more efficiently and quickly than during monotonous classes. Case studies are one of the methods aimed at developing students' critical thinking and their ability to independently evaluate information and formulate conclusions based on the acquired knowledge. The article highlights the origin, use and application of the case-study method in teaching the discipline "Age Physiology and School Hygiene" for students of higher education in the Secondary Education (Physical Culture) educational program. An analysis of this educational technology was conducted in the context of the formation of general and professional competencies of students, and the feasibility of using this method during practical classes in the discipline "Age Physiology and School Hygiene" was discussed. By its essence, the case study method combined such forms of organization of educational activities as lectures-disputes, simulation games based on "conference" and "investigation" scenarios, which allow you to focus on the basic principles of the functioning of the human body. The article provides examples of the successful use of the case study method in classes on the discipline "Age Physiology and School Hygiene", where its productivity and effectiveness are outlined. The analysis of the effectiveness of the formation and development of various competencies of higher education students, such as communicative, informational, logical, axiological, and emotional contact, which are present in an interactive environment, was carried out. It was concluded that the case study method is effective and has advantages compared to traditional teaching methods in the system of training students of higher education. It contributes to a deeper disclosure of the essence of physiological phenomena and biochemical processes that occur in the human body.
Keywords: Case method; interactive environment; students of higher education; case study method; age-related physiology and school hygiene